1993
DOI: 10.1177/089801019301100407
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Family Perceptions of Restraints

Abstract: Based on a holistic philosophy that aging persons' most primary need is that of autonomy and freedom, this qualitative descriptive study examined patients' and their family members' perceptions of the restraint procedure. Twenty-five restrained patients were interviewed, and 19 of their family members completed mailed surveys to describe their perceptions about restraints. Results indicated that the majority of patients (52%) expressed negative feelings about being restrained. Family members expressed a wide v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…1999, Marangos‐Frost & Wells 2000). In contrast, some studies found that nurses had no manifest ethical dilemmas (Hardin et al. 1994, Chien 2000, Werner & Mendelsson 2001).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…1999, Marangos‐Frost & Wells 2000). In contrast, some studies found that nurses had no manifest ethical dilemmas (Hardin et al. 1994, Chien 2000, Werner & Mendelsson 2001).…”
Section: Discussionmentioning
confidence: 95%
“…2001, Huang et al. 2003), on patients’ experience of being restrained (Strumpf & Evans 1988, Hardin et al. 1994, Gallinagh et al.…”
Section: Introductionmentioning
confidence: 99%
“…Negative attitudes about aging affect career choices and the quality of health care older adults receive (Gomez, Otto, Blattstein, & Gomez, 1985;Happell & Brooker, 2001;McKinlay & Cowan, 2003;Philipose, Tate, & Jacobs, 1991;Sainsbury, Wilkinson, & Smith, 1992;Spier & Yurick, 1989). Nurses with negative attitudes toward older persons, for example, often favor using physical and chemical restraints rather than less restrictive behavioral management strategies (Armstrong-Esther & Browne, 1986;Hardin et al, 1993;Helmuth, 1995;Wilkes, LeMiere, & Walker, 1998). Because healthcare behaviors are guided by attitudes (Stroebe, 2000), and education's role is to shape values and attitudes (Lutz, Elfrink, & Eddy, 1991), this paper focuses on the effect of curriculum changes on students' attitudes about aging.…”
Section: Please Scroll Down For Articlementioning
confidence: 96%
“…이처럼 억제대 사용에 대한 관심이 증 가하고 환자의 인권과 자율성 존중에 대한 권리와 요구가 강조 되면서 억제대를 적용받는 환자에게는 관심이 높아지고 있으 나 (Yeo & Park, 2006), 억제대를 적용한 환자를 지켜보는 가 족들이 겪을 수 있는 정서적 고통에 대해서는 간과되고 있는 실 정이다 (Macpherson, Lofgren, Granieri, & Myllenback, 1990). 중환자 가족의 요구를 분석한 Kwon과 Lee (1987) 억제대 적용에 대한 가족의 반응을 조사한 선행 연구 (Hardin, Magee, Vinson, Owen, & Hyatt, 1993;Kanski, Janelli, Jones, & Kennedy, 1996;Newbern & Lindsey, 1994 (Kang, 2003;Kim, 2001), 중환자실에서의 신체 억제 대 적용에 관한 연구 (Choi, 1999;, 중환자 실 간호사의 억제대 사용의도와 관련요인에 관한 연구 (Park, 1997), 중환자를 위한 억제대 개발과 그 사용 효과에 관한 연구 (Seo & Lee, 1996) …”
Section: 최근 보건의료분야에서는 의료지식과 기술의 팽창과 함께unclassified